2013
DOI: 10.1016/j.ccr.2013.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Par-4 Downregulation Promotes Breast Cancer Recurrence by Preventing Multinucleation following Targeted Therapy

Abstract: Summary Most deaths from breast cancer result from tumor recurrence, but the mechanisms underlying tumor relapse are largely unknown. We now report that Par-4 is down-regulated during tumor recurrence and that Par-4 down-regulation is necessary and sufficient to promote recurrence. Tumor cells with low Par-4 expression survive therapy by evading a program of Par-4-dependent multinucleation and apoptosis that is otherwise engaged following treatment. Low Par-4 expression is associated with poor response to neoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
108
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(125 citation statements)
references
References 31 publications
(38 reference statements)
13
108
1
3
Order By: Relevance
“…Even though BCL2 is mainly antiapoptotic, it is through the antiproliferative (46) and proapaptotic functions especially evident at higher expression levels, which BCL2 also exhibits (47), the positive prognostic value may emanate. Previous studies on the pro-apoptotic gene PAWR have found a negative prognostic value of low mRNA levels of PAWR in primary tumors, downregulation following NAC, but an unknown prognostic impact in residual disease (16). In the present study, PAWR was upregulated in response to chemotherapy, but no significant univariable prognostic value could be found in all patients.…”
Section: /Her2contrasting
confidence: 66%
See 1 more Smart Citation
“…Even though BCL2 is mainly antiapoptotic, it is through the antiproliferative (46) and proapaptotic functions especially evident at higher expression levels, which BCL2 also exhibits (47), the positive prognostic value may emanate. Previous studies on the pro-apoptotic gene PAWR have found a negative prognostic value of low mRNA levels of PAWR in primary tumors, downregulation following NAC, but an unknown prognostic impact in residual disease (16). In the present study, PAWR was upregulated in response to chemotherapy, but no significant univariable prognostic value could be found in all patients.…”
Section: /Her2contrasting
confidence: 66%
“…The genes were chosen from literature review on the basis of their being identified as (i) possible prognostic factors in residual disease at protein (4,(6)(7)(8)(9)(10) or mRNA level (11), (ii) as significantly up-or downregulated, but of unknown prognostic value in residual disease (12)(13)(14)(15)(16)(17)(18)(19)(20), (iii) as predictive of chemotherapy resistance (6,11,16,19,(21)(22)(23)(24)(25)(26)(27)(28)(29), and/or (iv) identified as possible prognostic factors over several previous datasets (26,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). In addition to the previously established prognostic factors ESR1 and ERBB2, the genes were also chosen to represent different pathways and biological processes of known implication in tumor progression or response to therapy, such as stemcellness (ALDH1A1, CD44, and STAT3), proliferation (TOP2A, MKI67, and AURKA), apoptosis (BCL2, BCL2L1, and PAWR), immunologic response (CD3D, CXCL13, and STAT1), epithelial-to-mesenchymal transition (EMT; SNAI1, SNAI2, SOX9, and TWIST), stromal activation (DECORIN, ...…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Par4 is believed to be a tumor suppressor and a crucial regulator of tumor cell survival. Emerging evidence has suggested that Par4 downregulation could be used as a prognostic factor in cancer (Alvarez et al, 2013). Another study indicated that the SAC domain of Par4 confers cancer resistance in transgenic mice without compromising normal viability or aging, and that it might have therapeutic significance (El-Guendy et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…29 Par-4 is a tumor suppressor and a critical regulator of tumor cell survival. 14,26 Subtle changes in regulation and alteration of Par-4 expression and localization may impact its biological function as a pro-apoptotic protein. In the present study, we provide evidence that the E3 ubiquitin ligase Fbxo45 interacts with Par-4 via its VASA-like sequence -a continuous six amino-acid peptide located in the N-terminal of Par-4 ( 68 ELNNNL 72 ), and that the interaction permits the polyubiquitylation and degradation of Par-4 in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Emerging data have implicated Par-4-induced multinucleation as a mechanism of cell death in oncogeneaddicted cells and establish Par-4 as a negative regulator of breast cancer recurrence. 26 In this study, we investigated whether endogenous Par-4 in cancer cells is regulated by proteasomal degradation and identified the cellular mechanism that regulates its ubiquitinmediated proteolysis thereby controlling its apoptotic function.…”
mentioning
confidence: 99%